Using technology to scale-up training and supervision of community health workers in the psychosocial management of perinatal depression: a non-inferiority, randomized controlled trial - Atif Rahman; Parveen Akhtar; Syed Usman Hamdani; Najia Atif; Huma Nazir; Iftikhar Uddin; Anum Nisar; Zille Huma; Joanna Maselko; Siham Sikander; Shamsa Zafar (Cambridge Prisms: Global Mental Health, 2019)
Background.The Thinking Healthy Programme (THP) is an evidence-based psychological intervention endorsed by the World Health Organization, tailored for non-specialist health workers in low- and middle-income countries. However, training and supervision of large numbers of health workers is a major challenge for the scale-up of THP. We developed a ‘Technology-Assisted Cascaded Training and Supervision system’ (TACTS) for THP consisting of a training application and cascaded supervision delivered from a distance.Methods.A single-blind, non-inferiority, randomized controlled trial was conducted in District Swat, a post-conflict area of North Pakistan. Eighty community health workers (called Lady Health Workers or LHWs) were randomly assigned to either TACTS or conventional face-to-face training and supervision by a specialist. Competence of LHWs in delivering THP post-training was assessed by independent observers rating a therapeutic session using a standardized measure, the ‘Enhancing Assessment of Common Therapeutic factors’ (ENACT), immediately post-training and after 3 months. ENACT uses a Likert scale to score an observed interaction on 18 dimensions, with a total score of 54, and a higher score indicating greater competence.Results.Results indicated no significant differences between health workers trained using TACTS and supervised from distance v. those trained and supervised by a specialist face-to-face (mean ENACT score M  =  24.97, s.d.  =  5.95 v. M =  27.27, s.d.  =  5.60, p  =  0.079, 95% CI 4.87–0.27) and at 3 months follow-up assessment (M  =  44.48, s.d.  =  3.97 v. M =  43.63, s.d.  =  6.34, p  =  0.53, CI −1.88 to 3.59).Conclusions.TACTS can provide a promising tool for training and supervision of front-line workers in areas where there is a shortage of specialist trainers and supervisors.